Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Matematika Tentang Perkalian dan Pembagian Pecahan - Rusli Rusli; Patri Janson Silaban; Lasma Silaban (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Student learning outcomes in learning fractions in elementary school are still low, to overcome this problem an effective model is needed. This research aims to describe the improvement in learning outcomes for multiplication and division of fractions using the PBL model in class V of SD Negeri 057761 Kwala Gebang. The research was carried out in two cycles, namely cycle I and cycle II. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The subjects of this research were 7 class V students at SD Negeri 057761 Kwala Gebang. Research results: RPP observations in cycle I averaged 83.33%, increasing to 97.22% in cycle II. In the observation results from the teacher aspect of cycle I, the average was 73.21%, increasing to 96.42% in cycle II. In the observation results from the student aspect of cycle I, the average was 64.28%, increasing to 92.85% in cycle II. Meanwhile, the learning outcomes of students in cycle I obtained 54.54% completeness, increasing to 95.45% completeness in cycle II. It can be concluded that the PBL model can improve student learning outcomes in learning multiplication and division of fractions in class V of SD Negeri 057761 Kwala Gebang.